Pengaruh Persepsi Manfaat dan Kemudahan Terhadap Minat Dalam Menggunakan QRIS (Studi Kasus Mahasiswa S1 Manajemen Universitas Dharma Andalas) - Nurhayani Nurhayani; Heru Aulia Azman (CV. ITTC INDONESIA, 2025)
This research aims to examine the effect of perceived usefulness and aese of use on students’ intention to use QRIS. The population of this study consists of undergraduate Management students at Dharma Andalas University, Padang, with a sample size of 110 respondents. The data were collected through questionnaires distributed directly to the respondents and were analyzed using SPSS version 25. The findings indicate that both perceived usefulness and aese of use have a significant effect on students’ intention to use QRIS. The coefficient of determination shows that these variables explain 39,1% of the variance in students’ intention to use QRIS, while the remaining 60,9% is influenced by other factors not examined in this study.